Ficus sycomorus extract reversed behavioral impairment and brain oxidative stress induced by unpredictable chronic mild stress in rats - Harquin Simplice Foyet; Serge Tchinda Deffo; Pascaline Koagne Yewo; Iulia Antioch; Stéphane Zingue; Emmanuel Acha Asongalem; Pierre Kamtchouing; Alin Ciobica (BMC, 2017)
Abstract Background Stress, regardless of its nature is nowadays recognized as one of the major risk factors for neuropsychiatric diseases, such as mood and anxiety disorders. The brain compared with other organs is more vulnerable to oxidative damage mainly due to its high rate of oxygen consumption, abundant lipid content, and relative insufficiency of antioxidant enzymes. Thus, the identification of neural mechanisms underlying resistance and vulnerability to stress is of crucial importance in understanding the pathophysiology of neuropsychiatric disorders and in developing new treatments, since the existing ones are for several reasons subject to increasing limitations. This study was aimed to assess the effects of hydromethanolic extract of Ficus sycomorus stem bark on depression, anxiety and memory impairment induced by unpredictable chronic mild stress (UCMS) in rats. Methods These effects were studied using anxiety-related behavior, depression-related behavior, anhedonia-like behavior and the Y maze task. Sucrose test was performed twice (before and after UCMS) to assess anhedonia in rats. Liquid chromatography-mass spectrometry analysis of the extract were performed. The antioxidant activities of the extract were assessed using total glutathione (GSH) content and malondialdehyde (MDA) level (lipid peroxidation) in the rat temporal lobe homogenates. Results The extract of F. sycomorus in a dose of 100 mg/kg significantly increased the sucrose consumption and the swimming time which had been reduced by the unpredictable chronic mild stress (p < 0.001). The extract also significantly reduced (p < 0.01) the latency time in the novelty-suppressed feeding test. In the elevated plus-maze, the extract (100 and 200 mg/kg) significantly reduced (p < 0.01) the time and the number of entries into the closed arms. The treatment with the extracts also significantly increased alternation in the Y-maze (p < 0.01 for 100 mg/kg). The extract significantly increased the total GSH content and reduced MDA level in rat temporal lobe. For the LC-MS analysis, the major compound in the extract was a flavonoid with formula C22H28O14. Conclusions F. sycomorus reversed the harmful effects of UCMS on mood and behaviors in rats and it possesses an antidepressant property that is at least in part mediated through the oxidative pathway.